The Influence of Brand Awareness and Brand Image on ASUS Laptop Purchasing Decisions of Management Students at Medan State University - Simanjuntak, Stephen; Marpaung, Jeremy Partogi; Simalango, Nora Florentina; Tarigan, Nimia Eliani Br; Sitindaon , Natanael; Siregar, Zulkarnain (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
Asus branded laptops have played a significant role among students. As the most widely used laptop brand by Indonesian consumers, a survey by the Katadata Insight Center (KIC) 2023 showed that 23.3% of respondents used Asus brand laptops in the last year. The type of research used in this research is quantitative research. The sample was used by 32 consumer respondents who purchased the Asus brand laptop. The test results showed that brand awareness did not have a significant influence on ASUS laptop purchasing decisions among the students of State University of Medan Management. The test result of the brand image hypothesis on Asus laptop purchase decisions showed an interesting finding. The brand image test results have a positive and significant impact on the purchase decision of Asus laptops. The results of the hypothetical test showed the brand Awareness does not significantly influence the purchase decisions of ASUS laptops among the student of State College of Medan. However, the interesting results also found that brand image has a positive, significant effect on the purchasing decision of the laptop ASUS. Brand awareness is not always a major determinant in purchasing decisions, especially in specific market segments such as students. Therefore, marketing strategies need to be more holistic and integrated with a focus not only on brand awareness but also on other factors relevant to consumer needs and preferences.